ASSESSING THE IMPACTS OF DISTRIBUTED GENERATION ON THE PROTECTION SCHEME OF A DISTRIBUTION NETWORK: TRANS AMADI 33 kV DISTRIBUTION NETWORK AS A CASE STUDY (Nigerian Journal of Technology, 2017)
Protection scheme of a radial network fails in coordination when additional power source is provided to the network via distributed generator other than a single source of power. Trans Amadi, 33 kV radial distribution network in Port Harcourt, Nigeria, has manually operated isolators backing up circuit breakers at substation. This arrangement alone cannot overcome rising issues due to bidirectional/multidirectional flow of power in a radial network whenever distributed generators are connected. There is therefore, a need for a protection scheme to be adopted whose devices can “coordinate” as well as offer a reliable protection to the network. This paper proposes a protection scheme design using coordinated behaviours of relay-operated reclosers and sectionalizers, as well as manages the effect distributed generators has, in a radial network using fault current limiter. Proposed protection scheme show results of a good coordination, mis-cordination and an improved coordination, without distributed generator, with distributed generator and with a fault current limiter respectively.  http://dx.doi.org/10.4314/njt.v37i1.27